Obtenção e utilização do extrato aquoso de jabuticaba (Myrciaria jabuticaba (Vell) Berg) em leite fermentado: l - Marina Campos Zicker (2011)
The jabuticaba is a fruit that has high acceptance as in its fresh form, as in its many industrialized food products. The nutritional importance of the jabuticaba is due to its richness in minerals, vitamins and phenolic compounds, which have several benefits to the human body such as antioxidant, anticancer and cardioprotective. The highest levels of these compounds are found in the fruit peel, and it is quite important to search for processes that look for the use of this fraction. Thus, this study aimed to produce a fermented milk jabuticaba flavored using extract prepared from the whole fruit. Three tests had been done in the fruit processing, differentiated by time (15, 30 and 45 seconds).The 45 seconds process was considered ideal, because it obtained the highest extraction of total phenolics and tannins. It was estimated that the concentration of aqueous jabuticaba led to polymerization / degradation of 65,6% of anthocyanins, despite increasing about 4 times the levels of total phenolics and tannins. The dilution of the jabuticabas extract and the sweetness of fermented milk jabuticaba flavored, considered ideal was 22% and 6.8% respectively. The two samples of fermented milk (flavored and no flavored) showed high acceptability (above 70%) in all attributes (appearance, odor, fruit flavor and consistency); the flavored sample showed significantly higher grades in the all attributes: aroma, taste and purchase intent in the two test session of acceptance and purchase intent (blind and informed test). Despite the improvement in all attributes in the test reported, this was not, in general, statistically significant. The parameters of jabuticabas fermented milk presented all determinations physicochemical and microbiological according to the Identity and Quality Standard.